Analysis of Selected Elements of the Quality Management System in a Production Company - Dominika STRYCHARSKA (Communications of International Proceedings, 2021)
The basis of any quality management system is the disclosure and improvement of non-conformities occurring in the company [Lock, 2002]. In the analyzed company, the products are inspected after each production stage in order to detect any non-conformities as soon as possible, after which the customer has submitted a complaint. This means that the quality management system in the analyzed enterprise is not transparent. Actions taken by a team of employees immediate. The HERCA method was used to verify the complaint. The purpose of this article is to analyse the quality of manufactured products and the procedures that are used in the analysed enterprise when a customer submits a complaint.
Keywords: Quality Management System; Pareto-Lorenz Analysis; Herca Method